Length-Weight and Length-Length Relationships in Freshwater Garfish Xenentodon cancila (Ham.) from Muriyadhar, Sunsari, Nepal - Subba, Bharat Raj; Mehta, Satya Narayan; Adhikaree, Shaligram (Journal of Natural History Museum, 2015)
Present paper attempts to describe length-weight (LW) and total length-standard length (TL and SL) relationships of fresh-water garfi sh Xenentodon cancila. Fish of different length and weight were caught using cast nets from Muriyadhar, Sunsari. The fish were kept in ice box in fresh condition and brought to fi sh laboratory, Department of Zoolog post Graduate Campus, Biratnagar. The data obtained from measurement were analysed using the formula W = aLb. The b values estimated for the total length and standard length in relation to body weight were 3.2202 and 3.2559 respectively. The values of b clearly indicate the allometric growth pattern and for total length and standard length relationship, the linear value of b was 0.3223. J. Nat. Hist. Mus. Vol. 26, 2012: 10-14